COMPETITIVENESS OF THE AGRI-FOOD SECTOR OF SERBIA THROUGH THE PERSPECTIVE OF UNIT VALUES OF EXPORTS AND IMPORTS - Marković, Milan; Simonović, Zoran (Economics of Agriculture, 2025)
The paper aims to investigate the export competitiveness of the Serbian agricultural and food (agri-food) sector at the divisional level. The core of the methodological approach is the calculation of export unit values (EUV) and import unit values (IUV) using data from the Statistical Office of the Republic of Serbia (SORS). The paper looks at export values, unit values, net exports, and competitiveness factors of the agri-food divisions for 2023. The obtained values indicate that Vegetables and Fruits is the division that has the largest share in agri-food exports, shows excellent terms of trade, and belongs to the group (category) of rare divisions that achieve competitiveness with quality. The Tobacco division is another important chapter of the agri-food sector, which also achieves non price competitiveness, has a positive terms of trade and significant net exports, which are very good circumstances in conditions of the necessary structural changes and sustainable export growth of the overall sector. These highly propulsive divisions show the greatest potential for development and increase in the degree of processing, so in the future they should be further supported by the measures of the agricultural policy of Serbia.